Time Varying Causality Relationships Between Bonds and Stock Markets: Findings of the Hatemi-J Dynamic Causality Test - Camgöz, Mevlüt (Muhasebe ve Finansman Öğretim Üyeleri Bilim ve Araştırma Derneği, 2022)
Economic developments and the uncertainty in risk factors can change the relationships between asset classes over time. Assuming that the relations between financial markets are of static in nature will result in erroneous investment and policy decisions, even if they are dynamic in reality. Focusing on the causality relationships between bond and stock markets, which has a central point of finance theory, this study aims to reveal whether there is symmetric and asymmetric causality relationship from bond market to the stock market, and if there is, whether this relationship changes over time. Dynamic symmetric and asymmetric causality tests developed by Hatemi-J (2021) are adopted as the analysis method. Dynamic symmetric and asymmetric causality test findings show that the causality relationship from bond market to the stock market changes over time. In conclusion, this study suggest that static models can lead to biased decisions such as hedging, diversification and asset allocation by demonstrating the structural changes and time dependency in the causal relationships between the bond and the stock market.

İktisadi gelişmeler ve risk faktörlerindeki belirsizlik durumu varlık sınıfları arasındaki ilişkileri zamana bağlı olarak değiştirebilmektedir. Finans teorisinde merkezi bir konumda olan tahvil ve hisse senedi piyasaları arasındaki nedensellik ilişkilerine odaklanan bu çalışma, tahvil piyasasından hisse senedi piyasasına doğru simetrik ve asimetrik nedensellik ilişkisinin olup olmadığını ve eğer varsa bu ilişkinin zamana bağlı olarak değişip değişmediğini ortaya koymayı amaçlamaktadır. Analiz yöntemi olarak Hatemi-J (2021) tarafından geliştirilen dinamik simetrik ve asimetrik nedensellik testleri benimsenmiştir. Analiz Ocak 1980 ile Nisan 2022 tarihleri arasında gerçekleştirilmiş ve ABD (Amerika Birleşik Devletleri) tahvil ve hisse senedi piyasası incelenmiştir. Dinamik simetrik ve asimetrik nedensellik testi bulguları tahvil piyasasından hisse senedi piyasasına doğru olan nedensellik ilişkisinin zamana bağlı olarak değiştiğini göstermektedir. Yani tahvil piyasası ile hisse senedi piyasası arasındaki nedensellik ilişkilerinde yapısal değişimler ve zaman bağımlılığı mevcuttur. Bu durumda statik modellerin riskten korunma, çeşitlendirme ve varlık dağılımı gibi kararlarda taraflı yönlendirme yapabileceği ortaya konulmuş olmaktadır.
Tahvil ve Hisse Senedi Piyasaları Arasında Zamanla Değişen Nedensellik İlişkileri: Hatemi-J Dinamik Nedensellik Testi Bulguları
Keywords: Business Administration; İşletme